ChemInform Abstract: A Highly Stereoselective Synthesis of New Styryl‐π‐Conjugate Organosilicon Compounds. Issue 45 (23rd October 2014) - Majchrzak, Mariusz; Hybsz, Milena; Kostera, Sylwia; Kubicki, Maciej; Marciniec, Bogdan
Abstract Silylative coupling of distyrylarenes with vinyltrimethylsilane provides new E, E‐bis(silyl)arenes with excellent selectivity.